2009
DOI: 10.1007/s11632-009-0013-6
|View full text |Cite
|
Sign up to set email alerts
|

Changes in root growth and relationships between plant organs and root hydraulic traits in American elm (Ulmus americana L.) and red oak (Quercus rubra L.) seedlings due to elevated CO2 level

Abstract: The relationships between plant organs and root hydrological traits are not well known and the question arises whether elevated CO 2 changes these relationships. This study attempted to answer this question. A pseudo-replicated experiment was conducted with two times 24 American elm (Ulmus americana L.) and 23 and 24 red oak (Quercus rubra L.) seedlings growing in ambient CO 2 (around 360 μmol·L -1 ) and 540 ± 7.95 μmol·L -1 CO 2 in a greenhouse. After 71 days of treatment for American elm and 77 days for red … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…The results obtained in the present study in OTCs and CCs demonstrated that increased atmospheric CO 2 reduced the severity of rust, increased plant growth and did not alter the concentration of essential oils in eucalypt plantlets (Figs 1-3). Increased plant growth as a result of increased CO 2 concentrations has been demonstrated in various species and is related to increased photosynthesis and other metabolic processes (Duff et al 1994;Pangga et al 2004;Cheng 2009;Runion et al 2010;Niu et al 2011). Few studies have evaluated the changes in the severity of diseases and pathogen life cycles resulting from increased atmospheric CO 2 concentrations (Eastburn et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained in the present study in OTCs and CCs demonstrated that increased atmospheric CO 2 reduced the severity of rust, increased plant growth and did not alter the concentration of essential oils in eucalypt plantlets (Figs 1-3). Increased plant growth as a result of increased CO 2 concentrations has been demonstrated in various species and is related to increased photosynthesis and other metabolic processes (Duff et al 1994;Pangga et al 2004;Cheng 2009;Runion et al 2010;Niu et al 2011). Few studies have evaluated the changes in the severity of diseases and pathogen life cycles resulting from increased atmospheric CO 2 concentrations (Eastburn et al 2011).…”
Section: Discussionmentioning
confidence: 99%